A Novel Convenient Synthesis of Pyridinyl and Quinolinyl Triflates and Tosylates via One-Pot Diazotization of Aminopyridines and Aminoquinolines in Solution - Kasanova A. Zh. Asiya Zhursunovna; Krasnokutskaya E. A . Elena Aleksandrovna; Beysembay P. S. Perizat Serikbolatkyzy; Filimonov V. D. Viktor Dmitrievich (2016, 2016)
Title screen